Prevalence of Pseudomonas aeruginosa and its Antibiotic Sensitivity Pattern - Pokharel, Khilasa; Dawadi, Bishwa Raj; Bhatt, Chandra Prakash; Gupte, Satish (Journal of Nepal Health Research Council, 2019)
Background: Pseudomonas aeruginosa is an opportunistic pathogen which causes most of the chronic infection in humans. This study was undertaken to determine the prevalence rate of Pseudomonas aeruginosa that is isolated from various clinical specimens along with its antibiotic susceptibility pattern. Methods: This descriptive cross sectional study was conducted in Kathmandu Medical College and Teaching Hospital (KMCTH) from February to May 2018. Pseudomonas aeruginosa isolated from various clinical specimens were processed in clinical laboratory, Department of Microbiology, KMCTH. Isolation, identification and sensitivity of Pseudomonas aeruginosa to antibiotics were measured. Results: A total of 7527 samples were been processed of which 46 isolates of Pseudomonas aeruginosa were obtained. Pseudomonas aeruginosa was isolated mainly from Pus, Wound swab, Sputum and Tracheal aspirate. Here 63.04% Pseudomonas aeruginosa isolates were resistant to Ceftazidime, 65.21% to Cefixime, 56.52% to Ceftriaxone and Cefotaxime followed by 56.52% to Piperacillin. Furthermore, the current study reveals antibiotics like Imipenem, Meropenem, Piperacillin/Tazobactam, Ciprofloxacin, Gentamicin, Amikacin and Tobramycin were found to be good choice for the treatment of infection caused by this organism. Conclusions: Continuous monitoring of antibiotic susceptibility pattern of Pseudomonas aeruginosa is essential and rational treatment regimens prescription by the clinicians is required to limit the spread of antimicrobial resistance. Keywords: Antibiotic resistance; clinical isolates; Pseudomonas aeruginosa.